Análisis de la relación binacional de integración económica: Colombia y Venezuela entre los años 2005 al 2019 - Johanna Milena Mogrovejo-Andrade; Nelson Emilio García-Torres; César Augusto Panizo-Cardona (Mundo Fesc)
This article describes economic and trade relations, especially in the last 15 years, where the interest in developing and promoting binational commercial alliance strategies allows the evolution of a border dynamic, planning, signing, and implementing economic complementarity agreements and conventions. Regional, national, and international interests are influenced by this economic dynamic, which impacts social, political, and cultural aspects. The research method used for the development of the study is quantitative since it seeks to quantify and analyze the behavior of the economic variables of the Colombian-Venezuelan bilateral relationship, based on numerical data and probabilistic studies. It allows us to understand how their commercial exchange has been during the period 2005-2019, reflected in the need to increasingly participate in global trade